Is the learning curve of the urology resident for conventional radical prostatectomy similar to that of staff initiating robot-assisted radical prostatectomy? - Rodrigo da Silva Pires; Cláudio William Alves Pereira; Luciano Alves Favorito (International Brazilian Journal of Urology, 2024)
ABSTRACT Introduction: The superiority of the functional results of robot-assisted radical prostatectomyis still controversial. Despite this, it is known that minimally invasive surgery obtains better results when analyzing blood loss, blood transfusion and length of stay, for example. Several studies have analyzed the impact of the resident physician's involvement on the results of urological surgeries. The simple learning curve for robot-assisted radical prostate surgery is estimated to be around 10 to 12 cases. Learning curve data for robotic surgeons is heterogeneous, making it difficult to analyze. Rare studies compare the results of a radical prostatectomy of an inexperienced surgeon starting his training in open surgery, with the results of the same surgeon, a few years later, starting training in robotic surgery. Objective: to analyze the results of open radical prostatectomy surgeries (ORP) performed by urology residents, comparing them to the results of robot-assisted radical prostatectomy (RARP), performed by these same surgeons, after completing their training in urology. Materials and methods: a retrospective analysis of the cases of only 3 surgeons was performed. 50 patients underwent ORP (group A). The surgeons who operated on the ORP patients were in the 3rd and final year of the urology residency program and beginners in ORP surgery, but with at least 4 years of experience in open surgery. The same surgeons, already trained urologists, began their training in robotic surgery and performed 56 RARP surgeries (group B). For the comparative analysis, data were collected on age, number of lymph nodes removed, surgery time, hospitalization time, drain volume, drain permanence time, indwelling bladdercateter (IBC) permanence time, positive surgical margin, biochemical recurrence, risk classification (ISUP), intra and postoperative complications, urinary incontinence (UI) and erectile dysfunction (ED). The console used was the Da Vinci Si, from Intuitive®. For statistical analysis, the Shapiro-Wilk test verified that the data did not follow normality, the Levene test guaranteed homogeneity, and the Mann-Whitney test performed the comparative analysis of the quantitative data. For the analysis of qualitative data, the Chi-square test was used for nominal variables and the Mann-Whitney U test for ordinal variables. Additionally, the Friedman test analyzed whether there was an improvement in the perception of UI or ED over the months, for each group individually (without comparing them), and the post-hoc Durbin-Conover test, for the results with statistically significant difference. We used a p-value < 0.05, and the Jamovi® program (Version 2.0). Results: there was no statistically significant difference between the groups for age, number of lymph nodes removed, positive surgical margin, biochemical recurrence, risk classification and urinary incontinence. Additionally, we observed that the surgical time was longer in group B. On the other hand, the length of stay, drain volume, drain time, IBC time, complication rate and levels of erectile dysfunction in the third and sixth months were higher in group A, when compared to group B. We also observed that there was no evolutionary improvement in ED over the months in both groups, and that there was a perception of improvement in UI from the 1st to the 3rd month in group A, and from the 1st to the 6th month, and from the 3rd to the 12th month, in group B. Conclusion: the learning curve of RARP is equivalent to the curve of ORP. In general, the results for the robotic group were better, however, the functional results were similar between the groups, with a slight tendency of advantage for the robotic arm.